Respuesta :

Space

Answer:

g(-4) = 3

General Formulas and Concepts:

Pre-Algebra

Order of Operations: BPEMDAS

  1. Brackets
  2. Parenthesis
  3. Exponents
  4. Multiplication
  5. Division
  6. Addition
  7. Subtraction
  • Left to Right

Algebra I

  • Function Notation

Step-by-step explanation:

Step 1: Define

g(x) = -x - 1

g(-4) is x = -4

Step 2: Evaluate

  1. Substitute in x:                    g(-4) = -(-4) - 1
  2. Multiply:                               g(-4) = 4 - 1
  3. Subtract:                              g(-4) = 3